From Epistemology of Suspicion to Racial Profiling: Hans Gross, Mobility, and Crime around 1900. Issue 2 (1st June 2019) - Hertz, Gal
Abstract : Hans Gross (1847–1915), the founder of Austro-Hungarian criminology, developed an epistemology of suspicion that targeted and profiled individuals as well as social and ethnic groups based mainly on their uprootedness and displacement. The scientific practices of observation and analysis he implemented in criminal investigations were anchored in epistemological assumptions that redefined and questioned both the object of study (namely, the criminal) and the subject (the investigator). By transferring scientific ideas and methods from the natural and social science into police work and judicial processes, Gross's study of crime merged biological and social perspectives. This meant the categories of deviancy were attached to foreignness and social difference, migration and effects of urban life. His epistemology was underlined by social Darwinism, and his forensics, far from being an objective study, advocated what is today known as racial profiling.